2024 Chinese guideline on the construction and application of medical blockchain# - Xiaoping Chen; Feng Cao; Qing Wang; Zhewei Ye; Xiaoping Chen; Zhewei Ye; Feng Cao; Weiqian Chen; Wei Cui; Donglei Feng; Guozhong Ji; Zhean Lin; et al. (Intelligent Medicine)
Abstract# It is worth mentioning that the Chinese version of this guideline has been published in the Chinese Journal of Multiple Organ Diseases in the Elderly (Chinese version) in the July 28, 2024 Guidelines and Consensus Column, Vol. 23, No. 7, pages 481-490.: With the rapid advancement of digitalization and intelligence in the medical field, a plethora of cutting-edge technologies are gradually being applied to revolutionize healthcare. In the medical data security privacy protection and artificial intelligence encryption computing, blockchain stands out due to its inherent characteristics of traceability, tamper-proofing, and high credibility. Although blockchain technology has been applied in various industries, its application in the medical field needs more driving force, and its development needs to be standardized. This clinical practice guideline is developed following the World Health Organization's recommended process, adopting Grading of Recommendations Assessment, Development and Evaluation in assessing evidence quality. Considering the integration of blockchain and medical scenarios, we focus on the value and implementability of practical medical applications and provide the guidance on the construction and application of medical blockchain. This practice guideline includesd 10 potential medical application scenarios and usage frameworks. It is worth highlighting that electronic medical record sharing, drug and device anti-counterfeiting, medical digital intellectual property protection, and public health management are considered to be the most easily implemented and effective medical scenarios. The recommendations in this guideline were formulated based on the consideration of stakeholder values and preferences, resource utilization, feasibility, and acceptability, may have a profound impact on the construction of medical blockchain-related scenarios in China and internationally.Registration: Practice Guidance Registration for Transparency (PREPARE) website (http://www.guidelines-registry.cn) Registration No. PREPARE-2023CN637.